Distributed mobility management in IP/LEO satellite networks - Wei Han; Baosheng Wang; Zhenqian Feng; Baokang Zhao; Wanrong Yu (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
By virtue of low end-to-end delay, the Low Earth Orbit (LEO) satellite network shows notable advantages in providing network services in global range. However, the high mobility of satellites leads to the constant changing location for terminals, which brings great challenges to the mobility management in LEO satellite networks. Existing mobility management schemes in satellite networks mainly borrow the idea from IP mobility solutions, such as MIP, MIPv6. Nevertheless, these schemes are all based on the centralized management architecture, which has exposed many defects in the terrestrial network, such as the scalability and performance problems. To eliminate these limitations, the Distributed Mobility Management (DMM) is proposed by deploying the distributed anchors to handle the traffic from mobile terminals. Currently, the feasibility of DMM in satellite networks has not been studied. In this paper, we present DIPS, a DMM based IPv6 mobility solution in LEO satellite networks. DIPS highlights a distributed location management architecture based on terrestrial gateways. To identify the merits and shortages, we make a comparison between the typical centralized scheme and DIPS. The theoretical analysis is presented to evaluate the performance on management cost. After that, the simulation with NS2.35 in the scenario of the Iridium system is conducted. Simulation results show that DIPS is an efficient scheme with preferable scalability in both management cost and latency.